Competition in Health Insurance - Schneider, Pia (World Bank, Washington, DC, 2012)
This knowledge brief presents the key findings of a recent World Bank report on, 'health insurance and competition'. The report examines whether competition helps multiple insurers better manage health expenditures by, for example, contracting with more efficient providers or directing consumers towards less costly care (i.e. consumers who use generic drugs pay lower premiums or co-payments). The Netherlands, Switzerland, Slovakia, and the Czech Republic are some of the countries that already have multiple and competing insurance systems in place.